2a∧2+(3a∧2-2a)-3(a∧2-a )先去括号,再合并同类项
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 17:05:47
2a∧2+(3a∧2-2a)-3(a∧2-a)先去括号,再合并同类项2a∧2+(3a∧2-2a)-3(a∧2-a)先去括号,再合并同类项2a∧2+(3a∧2-2a)-3(a∧2-a)先去括号,再合并同
2a∧2+(3a∧2-2a)-3(a∧2-a )先去括号,再合并同类项
2a∧2+(3a∧2-2a)-3(a∧2-a )先去括号,再合并同类项
2a∧2+(3a∧2-2a)-3(a∧2-a )先去括号,再合并同类项
=2a²+3a²-2a-3a²+3a
=(2a²+3a²-3a²)+(-2a+3a)
=2a²+a
2a²+3a²-2a-3a²+3a=2a²+a
2a^2+(3a^2-2a)-3(a^2-a )
=2a^2+3a^2-2a-3a^2+3a
=a^2(2+3-3)+a(3-2)
=2a^2+a
a∧3+2a∧2-a
【1】a+a=a×a a= [ ]【2】a×a=a÷a a=[ ]【3】a×a=a-a a=[ ] [4]a-a=a+a a=[ ]
计算(3a×a)+(2a×3a)+(3a×a)+[a×(a+2a+2a+2a+a)]
(通分) a/a^a^a+3a+2 ,a/a^a+2a+1 ,-1/3a+6
(a 1)(a 2)(a 3)(a
(a+2)(a+1)-a(a-3)
因式分解9a(a-4)∧2-6a∧2(4-a)-3(4-a)
(a*a+5a+3)(a*a+5a-2)-6因试分解
5a-【a+(5a-2a)-2(a-3a)-4a】
A∧2-A-3E=0,(A+E)∧-1=
2a∧2-a-3因式分解
计算;(a^3)^4+a^10×a^2-a×a^2-a*a^3*a^8
3a∧2-(2a∧2-2a)(3a-a∧2)
a-2a+3a-4a+5a-6a+...+99a-100a
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)